Autism Spectrum Disorder Learning Model for the Deaf at Saleh Children's Elementary School, Malang City - Maryam Luailik (Journal of Science and Research, 2025)
This study explores the learning process of children with special needs, particularly deaf and autistic children, whoexhibit distinct learning styles compared to typically developing children. The research is grounded in theunderstanding that every child has unique learning preferences, and children with special needs require inclusiveand adaptive educational approaches. This study employs a descriptive literature review of previous research onteaching strategies for deaf and autistic children. The findings indicate that deaf children learn more effectivelythrough visual media such as pictures, objects, videos, and written texts, while autistic children benefit fromlearning methods that emphasize emotional engagement, social skills, and direct interaction. In conclusion, thelearning process for children with special needs should consider individual characteristics, focusing on the use ofappropriate media, strategies, and approaches to achieve optimal educational outcomes.